2020
DOI: 10.1002/nop2.433
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial variation in caesarean delivery

Abstract: Aim The purpose of this study was to evaluate the variation in caesarean delivery rates across counties in Georgia and to determine whether county‐level characteristics were associated with clusters. Design This was a retrospective, observational study. Methods Rates of primary and repeat caesarean by maternal county of residence were calculated for 2008 through 2012. Global Moran's I (Spatial Autocorrelation) was used to identify geographic clustering. Characteristics of high and low‐rate counties were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The results of the full model agree with prior studies that both increased midwife density and independent midwifery practice are associated with a reduction of primary cesarean birth. [1][2][3]5,6 This study adds to the literature by demonstrating an interaction between independent midwifery practice and midwife density on the association with pregnancy outcomes. Currently, only 2 studies have examined the effect of state adoption of independent midwifery practice on primary cesarean, and neither study controlled for the density of midwives in the main analysis.…”
Section: Discussionmentioning
confidence: 61%
“…The results of the full model agree with prior studies that both increased midwife density and independent midwifery practice are associated with a reduction of primary cesarean birth. [1][2][3]5,6 This study adds to the literature by demonstrating an interaction between independent midwifery practice and midwife density on the association with pregnancy outcomes. Currently, only 2 studies have examined the effect of state adoption of independent midwifery practice on primary cesarean, and neither study controlled for the density of midwives in the main analysis.…”
Section: Discussionmentioning
confidence: 61%
“…According to the World Health Organization (WHO), CS should cover 10% to 15% of all deliveries at most [8,9]. However, the worldwide CS rate increased from 6.7% in 1990 to 21% in 2021, with 14.3% growth [8], and spatial variations in CS distribution are observed in different geographical areas [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth group of studies used geographical and spatial analysis to explain and interpret CS rates [11,19]. For instance, Vanderlaan et al [11] in Georgia identified counties with high-rate CS clusters had significantly lower access to midwives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used birth and C-section data from the March of Dimes and the National Center for Health Statistics during the years 2015-2019 across 3105 US counties [3]. Moran's I statistic was calculated to categorize individual counties as either Not Significant or as one of 4 statistically significant (p < 0.05) cluster classifications: High-High (H-H), High-Low (H-L), Low-High (L-H), Low-Low (L-L) [4]. In this attribution system, the first term designates the relative value of a given county compared to the national average; the second attribute reflects the relative value of neighboring counties compared to the national average.…”
mentioning
confidence: 99%